Comprehensive Review on Potent Derivatives of Rutin Towards Different Biological Activities - Saboo, Shweta; Sapkal, Shraddha; Nimbalkar, Vaishanavi (Pharmacognosy Reviews)
The greatest class of plant-derived polyphenolic chemicals are called flavonoids; they have a wide range of biological effects in both in vitro and in vivo mammalian cell systems. Rutin is one of more prominent flavonoid possessing wound healing, anti-inflammatory, antimicrobial, anti-mutagenic, anti-oxidant, and anti-HIV (Human Immunodeficiency Virus) property. The modification of Rutin’s structure aims to enhance the bioavailability, potency and target specificity. The exploration of Structure Activity Relationship (SAR) has been instrumental in guiding the design of its derivatives. The continued development of Rutin derivatives hold promise for novel therapeutic agents in the treatment of various diseases and health conditions. The chemical features, structure-activity connections, and therapeutic qualities of rutin and its strong derivatives that are helpful in drug development are briefly illustrated in this article.
Keywords: Anti-inflammatory; Antimicrobial; Antioxidant; Chemical properties; Polyphenols; Rutin derivatives.